Diseases of Mites and Ticks - Bruin, Jan.; Geest, Leo P. S. (Springer Netherlands, 2009)
The current collection of twenty-four papers is a mixture of primary research articles and literature reviews, presenting a broad overview of the developments in about all possible aspects of acarine diseases, stretching from basic pathology to microbial pest control. The pathogens include fungi, bacteria, and protozoa (as well as an occasional virus and unidentified organism), the hosts are mites and ticks from a great variety of taxa (e.g., Eriophyidae, Ixodidae, Oribatida, Phytoseiidae, Psoroptida, Tarsonemidae, Tetranychidae, Varroidae). These taxa include many infamous mites and ticks, which cause tremendous economical losses throughout the world, for example in greenhouse and field-grown agricultural crops, life stock (cattle, sheep), apiculture, and man. The taxa also include commercially available biocontrol agents, whose mass rearings need to be protected against pathogens.